Pendampingan Pembuatan Video Profil Sebagai Media Promosi Pada SDIT Mutiara Insan Sukoharjo - Hasman Budiadi; Setiyowati; Sri Siswanti (Jurnal Pengabdian Masyarakat Teknologi dan Pendidikan (MANTAP), 2025)
Mutiara Insan Sukoharjo Integrated Islamic Elementary School (SDIT) is a school that implements integrated education between science and Islam. SDIT is currently promoting by utilizing technology and social media. Promotions carried out include through the school website, social media and YouTube. Promotion using profile videos requires content updates, so it is necessary to create a new profile video, so that the information to be conveyed in the video is the latest activity. The mentoring process is carried out by assisting the school's public relations in making a profile video, starting from taking pictures or videos, the process of making it to uploading it to the media for promotion. The profile video made based on the scenario that has been made contains the school location profile, learning profile, facility profile, extracurricular activity profile, interest and talent activity profile and is closed with a speech from the Principal of Mutiara Insan Sukoharjo Elementary School